EXPRESSION OF MODALITY IN ALTERNATIVE INTERROGATIVE SENTENCES (Academia Science Repository, 2023)
In this article, alternative interrogative sentences, which are a type of interrogative sentences, and the expression of modal relations in them and the interpretation of the means of expressing modality are given.